From Islamism To Radicalism; Shifting Of Religious Understanding Movement Post-Reformation In Indonesia - Rahmah, Sitti; Museliza, Virna; Suryadi, Nanda; Malek, Jalaluddin Abdul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The history of Islam in Indonesia is often referred to as peaceful, friendly, and tolerant Islam. However, after the reformation in Indonesia, the Muslim community in this country experienced a shift in religious understanding that was quite serious to understand. Therefore, the important purpose of this article is to map the movement of religious understanding in Indonesia. This article is the result of library research, with a qualitative and philosophical approach. Data was obtained through reading various books, journals, and others related to the shift in religious understanding of Muslims in Indonesia. The data analysis technique in this study uses a three-step analysis procedure, namely: Data Reduction, Data Presentation, and Conclusion Drawing. The results of the study indicate that there has been a shift in the religious movement of Muslims in Indonesia towards Islamism, which is characterized by a strong desire to establish an Islamic caliphate or Islamic dawlah; enforcement of Islamic law; and jihad by fighting against infidels. This issue was then driven by the Islamic social movement both in society and in the world of education